The Ma'na Maghza's Approach to Self-Healing Verses in the Qur'an - Hakim, Lukman (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Cases of self-injury continue to increase year after year. In Indonesia - based on the Basic Health Research (Riskesdas) in 2018 - indicates that 19 million people aged 15 and above experience mental illness. Thus, this study aims to explain some self-healing techniques in the Qur'an as a solution to the occurrence of these cases and so that we keep mentally healthy. This research is pursued with the Ma'na cum Maghza approach, which is a method of interpreting the Qur'an by exploring the historical meaning and developing the meaning to the meaning of significance (maghza) to be applied in contemporary times. This study found that in Q.S al-Ankabut [29]: 45, the terms "al-S}ala>h" (prayer) and "tanha" (preventing) are interrelated, namely prayer can prevent the emergence of evil. Furthermore, prayer is not only a deterrent but, also to maintain the psyche because there is a relaxation process that brings together the components of prayer phrases and body sensation or muscle activity. In Q.S al-Ra'd [13]: 28, dhikr is accompanied by an acknowledgment of the greatness of Allah and an acknowledgment of his weakness, actually there has been a process of self-compassion and positive self-talk. In Q.S al-Baqarah [2]: 183, in the context of self-healing fasting is a gratitude therapy and contains aspects of kataris (purification of the soul). While in Q.S al-Taubah [9]: 103, the term "s}alla" is related to the term "sakanun", indirectly someone who prays, he will get peace because there is a process of confiding in it. In this verse, self-healing in the form of forgiveness is also found.